Determination of Flood Inuandation Areas in the City of Bingöl (Turkey) Using Geographic Information Systems and HEC-RAS - Murat Celiker; NILÜFER KOÇER; OSMAN YILDIZ (Doğal Afetler ve Çevre Dergisi)
Flood is among the most common natural disasters in Turkey. For this reason, it is very important to determine the flood spreading areas in advance, to reduce the flood risk and to ensure the safety of life and property accordingly. In this study, it is aimed to determine the flood water depths and inundation areas of Çapakçur, Gayt and Göynük streams passing through Bingöl Province center with the help of Geographic Information Systems (GIS) and HEC-RAS. Thus, hydraulic models of these streams passing through the city center were developed by the use of HEC-RAS for the peak flows obtained from synthetic unit hydrographs with return periods of 2, 5, 10, 25, 50, 100, 500 and 1,000 years. The data obtained from the up-to-date maps of the study area with 1/1,000 scale were defined to the model by HEC-GeoRAS working on ArcGIS. According to the flood inundation maps, which were prepared in the GIS environment using the hydraulic model results obtained with the help of HEC-RAS, the maximum flood water depth varies between 8.12 and 9.62, and the maximum flood inundation area ranges from 635,402 to 1,561,982 m2 for the flood peaks considered in the study. The flood inundation maps obtained in this study can be used as an important data source for the future settlement and development plans of the region.